Paradox of the safety in the urban space - Trammer, Hubert (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2017)
Coexistence of pedestrian traffic with the car traffic or tram traffic in many cases means better effects than their clear separation. It’s the case in the field of the quality of staying in the city, but paradoxically also in the field of safety. In this publication are shown the examples of such solutions.